At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
That symbol between f and g means to multiply.
yes it does
Ok, do you need anymore help then?
lol yes I don't get the problem
How do I do it?
Take the expression that f is equal to and multiply it to the expression g is equal to.
i.e. stick a times sign between them, or just write them next to each other
How do I find out what each expression stands for?
It is given to you f(x)=log_10(x) and g(x)=5x-2
Yeah so how do I solve the expression?
There is really nothing to do here just replace f(x) with what it equals and replace g(x) with what it equals in the expression f(x)*g(x)
Like if I said f(x)=5x and g(x)=sin(x) then f(x)*g(x)=5x*sin(x)=5xsin(x)
you lost me
How about the example, if f(x)=2x and g(x)=e^x then f(x)*g(x)=2x*e^x=2xe^x
Ok now I'm understanding you more, but i'm getting confused after the = sign.
Or here is another example if f(x)=4x-2 and g(x)=9x then f(x)*g(x)=(4x-2)(9x) And if you want you could distribute and say f(x)*g(x)=(4x)(9x)-2(9x)=36x^2-18x
All I'm doing is saying what f(x)*g(x) is given what f(x) equals and g(x) equals
I'm just replacing f(x) with what it equals and replace g(x) with what it equals
see I donnt know how to get the equal part
You put an equal sign
Or do you mean the part that follows the equal sign
the part that follows the equal sign is f(x)*g(x)
after the equal part
just the expressions they are equal to instead of saying f(x)*g(x)
Like if I said f(x)=3 and g(x)=2 what is f(x)*g(x)?
yes or you could say 3*2 without simplifying right
so what is complicated about what your problem is asking then?
ok.. I'll be right back.
then you are done